The swedish covid‐19 intensive care cohort: Risk factors of ICU admission and ICU mortality. Issue 4 (8th February 2021) - Ahlström, Björn; Frithiof, Robert; Hultström, Michael; Larsson, Ing‐Marie; Strandberg, Gunnar; Lipcsey, Miklos
Abstract : Background: Several studies have recently addressed factors associated with severe Coronavirus disease 2019 (COVID‐19); however, some medications and comorbidities have yet to be evaluated in a large matched cohort. We therefore explored the role of relevant comorbidities and medications in relation to the risk of intensive care unit (ICU) admission and mortality. Methods: All ICU COVID‐19 patients in Sweden until 27 May 2020 were matched to population controls on age and gender to assess the risk of ICU admission. Cases were identified, comorbidities and medications were retrieved from high‐quality registries. Three conditional logistic regression models were used for risk of ICU admission and three Cox proportional hazards models for risk of ICU mortality, one with comorbidities, one with medications and finally with both models combined, respectively. Results: We included 1981 patients and 7924 controls. Hypertension, type 2 diabetes mellitus, chronic renal failure, asthma, obesity, being a solid organ transplant recipient and immunosuppressant medications were independent risk factors of ICU admission and oral anticoagulants were protective. Stroke, asthma, chronic obstructive pulmonary disease and treatment with renin‐angiotensin‐aldosterone inhibitors (RAASi) were independent risk factors of ICU mortality in the pre‐specified primary analyses; treatment with statins was protective. However, after adjusting for the use of continuous renal replacement therapy, RAASi were no longer an independent risk factor. Conclusion: In our cohort oral anticoagulants were protective of ICU admission and statins was protective of ICU death. Several comorbidities and ongoing RAASi treatment were independent risk factors of ICU admission and ICU mortality.